Neonatal assessment in the delivery room – Trial to Evaluate a Specified Type of Apgar (TEST-Apgar) - Rüdiger, Mario (BMC Pediatr, 2015)
BACKGROUND: Since an objective description is essential to determine infant’s postnatal condition and efficacy of interventions, two scores were suggested in the past but weren’t tested yet: The Specified-Apgar uses the 5 items of the conventional Apgar score; however describes the condition regardless of gestational age (GA) or resuscitative interventions. The Expanded-Apgar measures interventions needed to achieve this condition. We hypothesized that the combination of both (Combined-Apgar) describes postnatal condition of preterm infants better than either of the scores alone. METHODS: Scores were assessed in preterm infants below 32 completed weeks of gestation. Data were prospectively collected in 20 NICU in 12 countries. Prediction of poor outcome (death, severe/moderate BPD, IVH, CPL and ROP) was used as a surrogate parameter to compare the scores. To compare predictive value the AUC for the ROC was calculated. RESULTS: Of 2150 eligible newborns, data on 1855 infants with a mean GA of 28(6/7) ± 2(3/7) weeks were analyzed. At 1 minute, the Combined-Apgar was significantly better in predicting poor outcome than the Specified- or Expanded-Apgar alone. Of infants with a very low score at 5 or 10 minutes 81% or 100% had a poor outcome, respectively. In these infants the relative risk (RR) for perinatal mortality was 24.93 (13.16-47.20) and 31.34 (15.91-61.71), respectively. CONCLUSION: The Combined-Apgar allows a more appropriate description of infant’s condition under conditions of modern neonatal care. It should be used as a tool for better comparison of group of infants and postnatal interventions. TRIAL REGISTRATION: clinicaltrials.gov Protocol Registration System (NCT00623038). Registered 14 February 2008. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12887-015-0334-7) contains supplementary material, which is available to authorized users.